HR option bundles for the management of human capital investment: Risks and performance implications for CSEZ locators - Villanueva, Arlyn Juanita Sicangco (Animo Repository, 2003)
This paper examines using Structural Equation Modeling (SEM), the proposition that--human capital investments could involve a paradigm shift that would allow management to effectively employ bundles of human resource options, considering specific contingencies such as organization factors, strategies pursued and company risks and their effects on business performance and strategic effectiveness. In order to support and prove the proposition, the Bhattacharya and Wright (2000) framework, which proposed HR options for specific HR risks, was tested as antecedents to HR practices/real options. The framework was expanded to determine the consequences of these HR options and to model the interactions among firm variables (industry type, number of employees, age since establishment, and age at Clark Special Economic Zone (CSEZ), business strategy--(growth and defensive), HR risks (skills obsolescence, uncertainties of volume, and uncertainties of costs), HR options (growth options, options to alter scale of operations, and options to alter costs), business performance and strategic effectiveness. Using a two-stage structural equation modeling on the responses of a sample of locator firms at CSEZ to a constructed questionnaire on perceptual measures of the variables, a model was formulated to allow firms to manage their human capital investment risks. Support for the framework was indicated in the significant relationships skills obsolescence and HR growth options, and uncertainties of volume and HR options to alter scale. HR growth options were also shown to be significantly explained by growth strategy and a latent skills-oriented HR options common factor, aside from its HR risk pair. Hr options to alter scale had defensive strategy, uncertainties of volume, and latent skills-oriented HR options common factor, and years of operation at CSEZ, as significant antecedents, and led to positive business performance outcomes, and, as a consequence of this link, to strategic effectiveness. Significant fit of the estima